The frequency of urinary incontinence among Polish women after 40 years old - Wróbel, Romana; Kremska, Anna; Kołodziej, Bernadeta; Barnaś, Edyta (European Journal of Clinical and Experimental Medicine, 2013)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Urinary incontinence is defined as involuntary leakage of urine. The disease commonly affects women and is classified by WHO as one of the most important medical problem in XXI century. Currently, the classification of urinary incontinence is composed of 5 main types: stress, urge, mixed, overflow and extra urethral incontinence. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Objectives. The aim of this paper is to present this disease and analyze the frequency of the occurrence of urinary incontinence among women in Podkarpacie – Poland. Material and methods. In the period from November 2009 to March 2010, 300 women over 40 were given questionnaires including questions about the situations in which they suffer from involuntary urinary incontinence. The method that was used was an UDI questionnaire and original surveys. The completed questionnaires in the number of 242 were obtained and then served as material to work with. The received material was analyzed on the basis of Statistica 7.0 programme. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean age of women was 54 years. The frequency of occurrence of urinary incontinence among Polish women is 68%. 38% of them declared stress incontinence, 22% urge , 4% overflow, 5% extraurenthral and 31% mixed incontinence. The frequency has been increasing along with the body mass index. Urinary incontinence was present among 70% who delivered, and 53% who did not. 75% postmenopausal and 63% premenopausal women were also incontinent. The disease was diagnosed among 66% physically and 55% mentally working women. There was a strong correlation between pelvic organ prolapsed and different forms of urinary incontinence. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. Urinary incontinence was the most common complaint in contemporary women of all ages. The increase in the frequency of urinary incontinence among Polish women depends on their age, weight, and is increasing among women who has not deliver yet , who perform physical work or those who are postmenopausal. In order to reduce the percentage of the disease occurrence it is essential to educate the society and conduct scientific research in this field. It is also important to develop a proper attitude among people and to form pro-healthy behaviors among society.